The Role of Entrepreneurship Education in Higher Education Institutions - Thobeka Ncanywa; Noluntu Dyantyi (E-Journal of Humanities, Arts and Social Sciences, 2022)
Entrepreneurship education affords people with skills that display the characteristics of risk-taking, being involved in making informed decisions, creativity and innovation. Entrepreneurship education can provide teaching approaches to changing problems into business opportunities to assist the university community in addressing graduate employability. In addition, it can provide post-COVID-19 pandemic solutions to their start-ups or existing businesses. The paper explores the role of entrepreneurship education in Higher Education Institutions by discussing the effective and sustainable teaching methods that can be used in entrepreneurship teaching, employing a qualitative thematic review methodology. The entrepreneurship ecosystem can be key when higher education institutions are engaged in the transformation process of offering entrepreneurship education to their community. This paper explores the following themes: entrepreneurial education needs in entrepreneurial institutions, stakeholders involved in the provision of entrepreneurship education, and a sustainable business model as a product of entrepreneurship education. The present paper recommends that universities adopt a participatory approach to teaching and learning entrepreneurship as this can play a crucial role in building their structures to be economically active. Furthermore, it addresses graduate unemployment; provides recovery strategies to reboot businesses in communities, especially after the COVID-19 pandemic; and how to position themselves as entrepreneurial institutions.